Analisa uji ketahanan fatigue Aluminium scrap hasil remelting sepatu rem (brake shoe) terhadap variasi beban menggunakan tipe rotary bending - Wahyono, Wahyono; Nugroho, Eko; Handono, Sulis Dri; Budiyanto, Eko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
Used brake shoes are a component of a two-wheeled vehicle that has a type of aluminum material. Therefore, we can do remelting aluminum from brake shoes that can no longer be used for advanced application use and utilization of brake shoe waste which still has a sale value. This study aims to determine the best value or the one that approximates the fatigue limit endurance value of each loading variation given to the specimen and to determine the characteristics of the fracture surface from the differences in given loading. The research method used for fatigue testing is by using a literature study and direct observation or observation. Before doing the fatigue testing, first, do the tensile test to get the yield strength value where this value is used for the loading that will be given to the fatigue test, the loading variations are given for the fatigue test are 40%, 50%, and 60 % of the yield strength value. From the results of fatigue testing at a load of 60% with the stress of 100.2 MPa and a given load of 3.81 kg, it can be seen that the value of material fracture at 27,421 cycles and in the timeframe 00:18:16. Then at 50% loading with the stress of 83.5 MPa and a given load of 3.18 g, it can be seen that the fracture value of the material in the 51,659 cycles in the fracture period is 00:34:35. Then in the next test with a load of 40% and given the stress of 66.8 MPa and a load of 2.5 kg, it is known that the fracture value of the material in the 106,930 cycles in the fracture period reaches 01:11:17. From the test data, it can be concluded that the ratio between cycle and time with voltage is inversely proportional, that is, the smaller the voltage the greater the cycle and time obtained, and vice versa, the greater the voltage, the smaller the cycle and time will be obtained. Keywords: Used brake shoes, Aluminum, Remelting, load variation, fatigue test.